Parameterized Complexity of Graph Burning - Kobayashi, Yasuaki; Otachi, Yota (Algorithmica, 2022)
Graph Burning asks, given a graph G = ( V , E ) and an integer k , whether there exists ( b 0 , ⋯ , b k - 1 ) ∈ V k such that every vertex in G has distance at most i from some b i . This problem is known to be NP-complete even on connected caterpillars of maximum degree 3. We study the parameterized complexity of this problem and answer all questions by Kare and Reddy [IWOCA 2019] about the parameterized complexity of the problem. We show that the problem is W[2]-complete parameterized by k and that it does not admit a polynomial kernel parameterized by vertex cover number unless NP ⊆ coNP / poly . We also show that the problem is fixed-parameter tractable parameterized by clique-width plus the maximum diameter among all connected components. This implies the fixed-parameter tractability parameterized by modular-width, by treedepth, and by distance to cographs. Using a different technique, we show that parameterization by distance to split graphs is also tractable. We finally show that the problem parameterized by max leaf number is XP.